Keynote colection for Young bands - HUMMEL, Herman A. (Rubank Inc., 1962)
Step alongnMoonlight BaynTrophy winnernSouthern skiesnToyland waltznEntrance of the MikadonSouble your pleasurenYankee doodle boynSong of the night